STUDENTS’ GRAMMATICAL COLLOCATION ERRORS AND ITS’ IMPLICATION IN TEACHING WRITING - Fadlilah, Sayyidatul (IJET (Indonesian Journal of English Teaching), 2016)
The Regulation of Minister of Education and Culture of the Republic of Indonesia number 49 2014 on National Standard of Higher Education stated that National Standard Research is the minimum criterion of research on higher education system in force in the entire territory of the Republic of Indonesia. The study was conducted according to the rules of the activities and the scientific method systematically to obtain information, data, and information related to the understanding and/or testing of a branch of knowledge and technology. Based on the background the researcher states the following questions of the research: 1) What kinds of grammatical collocation errors were found in students’ thesis? 2) what is the implication of students’ grammatical collocation errors in teaching Writing. The researcher analyzed five major types of grammatical collocation error found in English department students’ thesis. The classification of five major types of English grammatical collocation error will make it easy to understand English grammatical collocations. The first type of English grammatical collocation error is collocation consisting of twelve English verb patterns (G8) which have different grammatical structures as the most challenging followed by (G7), (G1), (G4, (G5). As for the implication of those errors made by students is that the lecturers must include the discussion of collocation in teaching Writing.